Sport Practice, Fluid Reasoning, and Soft Skills in 10- to 18-Year-Olds - Feraco, Tommaso; Meneghetti, Chiara (Frontiers in Human Neuroscience, 2022)
Engaging in physical activity and sports has been associated with various cognitive abilities and other personal characteristics. The contemporary link between doing sports and personal attributes such as soft skills and an individual’s cognitive abilities have yet to be investigated, however. This study aims to analyze the association between years of practicing a sport, cognitive abilities (in terms of fluid reasoning), and personal attributes (in terms of soft skills). A large sample of 1115 individuals (10-18 years old) completed the Cattel test (measuring fluid reasoning) and answered a questionnaire measuring six soft skills (adaptability, curiosity, initiative, leadership, perseverance, and social awareness). A multivariate regression analysis show that, after controlling for age and gender, participants’ years of practicing a sport were positively associated with three soft skills (i.e., initiative, leadership, and perseverance) and with fluid reasoning. No differences emerged between team and individual sport practitioners. Our findings suggest an association between practicing sports, which entails more than just physical activity, and both cognitive abilities (fluid reasoning) and other important personal characteristics, such as soft skills.